Perancangan Sistem Aplikasi Penentuan Jurusan di SMKN 1 Bukittinggi Berdasarkan Hasil Tes Dengan Menggunakan Bahasa Pemograman PHP - Heru Firdan Al-Ghovari1; Liza Efriyanti; Supratman Zakir; Riri Okra (Universitas Pahlawan Tuanku Tambusai, 2022)
The development of computer technology today has provided all information quickly and with a high degree of accuracy, so that its use extends to other fields, especially education. The educational process, if equipped with information technology that suits your needs, will provide convenience in the world of education itself. Especially at SMKN 1 Bukittinggi, there are still many students and prospective students who have problems in determining and choosing majors, with minimal provisions, some students are already registered, they just know the major they are taking and other majors, because of this discrepancy, some students want to change majors, drop out of school, and repeat because the major they choose does not match their interests or abilities, this problem will waste their youth time . This is what lies behind the author to design a fee system, majors at SMKN 1 Bukittinggi based on test results using the PHP programming language. Keywords: Treatment Systems, Department, R&D Development Research, PHP.